2020
DOI: 10.1002/jclp.22943
|View full text |Cite
|
Sign up to set email alerts
|

Affectivity in schizophrenia: Its relations with functioning, quality of life, and social support satisfaction

Abstract: Objective: To evaluate the relationship between affectivity and sociodemographic and clinical characteristics, quality of life, functioning, and social support satisfaction in schizophrenia. Method: Cross-sectional study of a sample of 282 schizophrenic patients. An interview was performed using a sociodemographic and clinical questionnaire and scales to evaluate positive and negative affect, quality of life, social support satisfaction, and functioning. Results: Participants' employment status, gender, whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…The influence of social contact in different contexts and its effect on the presence of mental and physical disorders has been object to studies around the world. Some studies have shown that social support has a protective role in chronic diseases, promoting stress reduction and relieving patients' symptoms (Greenberg et al, 2014; Pinho et al, 2020; Studart et al, 2016, 2015). Furthermore, an earlier age at onset may contribute to impair functioning among BD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of social contact in different contexts and its effect on the presence of mental and physical disorders has been object to studies around the world. Some studies have shown that social support has a protective role in chronic diseases, promoting stress reduction and relieving patients' symptoms (Greenberg et al, 2014; Pinho et al, 2020; Studart et al, 2016, 2015). Furthermore, an earlier age at onset may contribute to impair functioning among BD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Family psychoeducation is one of the interventions that can improve the quality of that support, allowing the family to have a deeper perception of schizophrenia [9]. As far as other environmental factors are concerned, studies have shown that the higher the perception of social support or satisfaction with it, the better the effectivity and quality of life [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms and problems related to schizophrenia affect the individual, family members, and society in many ways. Studies in the literature have revealed that schizophrenia has negative effects that reduce the quality of life of the individual and compel the family and society due to frequent recurrences 2,3 . Recently, perceived social support has been suggested to be a protective factor for quality of life in patients diagnosed with schizophrenia 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…revealed that schizophrenia has negative effects that reduce the quality of life of the individual and compel the family and society due to frequent recurrences. 2,3 Recently, perceived social support has been suggested to be a protective factor for quality of life in patients diagnosed with schizophrenia. [4][5][6] Social support is defined as any material and moral support provided by the close circle of the individual.…”
mentioning
confidence: 99%